THE ROLE OF ETHNOTURISM AND TOURISM CULTURE IN THE ECONOMIC TRANSFORMATION PROCESSES OF THE CITIES OF THE FERGANA VALLEY - OmonovAzamatjon Iqrorjon ogli (Western European Studies, 2025)
This article analyzes the role of tourism culture in the development of economic transformation processes and its impact on the economy, the importance of rituals and holidays in the system of intangible cultural heritage of Uzbek culture not only on a global scale, but also on the development of ethnotourism and tourist services, the impact of ethnotourism on the development of ethnotourism and the causes of problems encountered in this process, the impact of folk games on ethnotourism culture in the development of ethnotourism and the need to conduct scientific research on the implementation of scientific approaches in practice
Keywords: driver; investment; free economic zone; tourism